DETEKSI DINI TUMBUH KEMBANG ANAK BALITA DALAM UPAYA PENCEGAHAN DAN PERCEPATAN PENURUNAN STUNTING DI DESA SUMBERTEBU KECAMATAN BANGSAL KABUPATEN MOJOKERTO - Ika Yuni Susanti; Dyah Siwi Hety; Zulfa Rufaida; Sari Priyanti; Sri Wardini Puji Lestari (Jurnal Pengabdian Masyarakat, 2025)
The problem of stunting in toddlers is still a health problem, especially in developing countries. One of the efforts that can be made to reduce the incidence rate is increasing parental knowledge about stunting, namely how to prevent and treat and improve the nutrition of toddlers so that their growth and development can be maximized. The community service activities carried out aim to prevent stunting through early detection of growth and development and improving the nutritional status of toddlers. The activities were carried out by a team of lecturers from the Midwifery Professional Education Study Program, Majapahit Health College in Sumbertebu Village, Bangsal District, Mojokerto Regency. The activity uses lecture, simulation and role-playing methods and conducts growth and development checks on toddlers from September to November 2024. The results of community service activities have been attended by 53 mothers and toddlers, a significant increase in knowledge of 64% was obtained and in toddlers who underwent growth and development checks by measuring height, weighing and early detection with the Pre-Screening Questionnaire for Development (KPSP) it was concluded that there were no toddlers who were heading towards stunting or experiencing developmental delays. Health education can increase participants' knowledge in understanding the material and are willing to actively come routinely to participate in posyandu activities and know the schedule for growth and development checks properly. This activity is expected to increase mothers' knowledge about the implementation of early detection of growth and development in efforts to handle stunting, so as to prevent growth and development delays in toddlers